Biliary Fascioliasis in Chronic Calcific Pancreatitis Presenting with Ascending Cholangitis and Biliary Stricture - Pattarapuntakul, Tanawat (Case Rep Gastroenterol, 2019)
Biliary fascioliasis is a rare infection of the hepatobiliary system. In human, it is known to present with two main phases; acute phase (hepatic phase) presenting with abdominal pain or abnormal liver biochemistry then chronic phase (biliary phase) presenting with biliary obstruction or cholangitis. Optimal treatment of biliary fascioliasis consists of endoscopic retrograde cholangiography with removal of the parasite and single oral dose of triclabendazole. We report a rare case of biliary fascioliasis in chronic calcified pancreatitis who presented with ascending cholangitis and biliary stricture. A 63-years-old Thai man was referred to our hospital for treatment of clinical symptoms severe cholangitis. Magnetic resonance cholangiopancreatography showed evidence of distal common bile duct stricture associated with chronic calcific pancreatitis. ERCP was performed, that found a few amorphous filling defects in the common bile duct and distal biliary stricture. After removal of the foreign body of what seems to be a fluke parasite followed with single oral dose triclabendazole thereafter, the clinical symptom was improved dramatically.